Clinical Presentation and Bacteriology of Diabetic Foot Ulcers at Mulago Hospital: A Prospective Case Series Study. - Pario, Aldo Justin; Nakwagala , Frederick Nelson; Kamya , Moses; Ejalu, David Livingstone (Student's Journal of Health Research Africa, 2022)
Background: Diabetic foot ulcer is a common cause of mortality among patients admitted to Mulago hospital. Peripheral neuropathy and peripheral arterial disease are the major risk factors for diabetic foot ulceration and the severity of these two conditions may determine treatment options and ulcer outcomes. General objective: The study assessed the clinical presentation of foot ulcers in diabetic patients and identified the common bacterial isolates from diabetic foot ulcers and their susceptibility patterns. Methods: This was a prospective study involving 60 consecutive patients with diabetic foot ulcers admitted to the endocrinology unit at Mulago hospital between July and December 2010. Patients were recruited after the provision of written informed consent. Deep tissue swabs from the ulcers were then taken at debridement for both aerobic and anaerobic cultures and susceptibility tests using standard microbiological methods. Results: Of the 60 patients, 57% had neuroischemic foot ulcers, 18% had neuropathic ulcers, 18% had ischemic ulcers and 7% had unclassified ulcers. 98.3% of the samples grew 93 aerobic bacteria and no anaerobe was isolated. Polymicrobial infection occurred in 41% of samples of which 10% had mixed growth. 80.6% of the isolates were Gram-negative aerobes, mainly E.coli Klebsiella, Pseudomonas, and Proteus while eighteen (19.4%) were Gram-positive, mainly Staphylococcus aureus and Enterococcus faecalis. The prevalence of MuMultidrug-resistant organisms (MDRO) was 84% and Methicillin-resistant staphylococcus aureus (MRSA) was 60% while Extended-spectrum beta-lactamases (ESBL) was 43.5%. Conclusion: Diabetic foot ulcers were mostly neuroischemic with moderate neuropathy severity. Infection was mostly due to aerobic Gram-negative organisms with a high prevalence of MDRO, ESBL, and MRSA. Most isolates were susceptible to vancomycin, imipenem, and ciprofloxacin. Recommendation: Deep tissue culture and sensitivity tests should be done to make appropriate antibiotic choices for diabetic patients with foot ulcers.